Low-temperature repair method of retired lithium iron phosphate positive electrode material and application of low-temperature repair method
By using Lewis alkali reagent for liquid phase lithiation reaction at low temperatures, the problem of cumbersome liquid phase repair methods and large energy consumption of retired lithium iron phosphate is solved, and the direct regeneration and performance improvement of retired lithium iron phosphate is achieved.
Patent Information
- Application Number
- CN202411982656.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, the liquid phase repair method of retired lithium iron phosphate is complicated, the energy consumption is large, and it is difficult to achieve homogenized and combined repair of materials of different levels of retirement.
By introducing Lewis alkali reagent with strong electron donation, liquid phase lithiation reaction is carried out at low temperature, and direct regeneration of decommissioned lithium iron phosphate is achieved.
This method can realize direct recycling of decommissioned lithium iron phosphate without pressurization at low temperatures, reducing production costs and energy consumption. The repaired lithium iron phosphate has excellent performance and excellent circulation stability.
Smart Images

Figure CN119660703A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a low-temperature repair method for retired lithium iron phosphate positive electrode materials and applications thereof, belonging to the technical field of battery materials. Background Art
[0002] Lithium iron phosphate cathode materials have emerged as cathode materials for automotive power batteries due to their stable olivine structure and green, readily available raw materials. In 2023, the installed capacity of lithium iron phosphate power batteries in China hit a new record high (~261.0GW·h), accounting for 67.3% of the total installed capacity. Therefore, the efficient and accurate repair and regeneration of discarded lithium iron phosphate cathode materials is of great significance to the new energy storage market and the ecological environment on which human beings depend for survival.
[0003] At present, the recycling method for retired lithium iron phosphate batteries in the industry is mainly a combination of hydrometallurgy and pyrometallurgy, and the recycling path is mainly based on hydrometallurgy. However, with the rapid decline in the price of lithium carbonate / lithium hydroxide in recent years, the profit margin of the traditional recycling model has been significantly reduced. Considering the problems caused by the high energy consumption and secondary pollution of the current traditional recycling model, the transformation of the recycling path for retired lithium iron phosphate positive electrode materials is imminent. The strategy of regenerating retired lithium iron phosphate into fresh lithium iron phosphate through lattice relithiation is called direct regeneration. Different from the pyrometallurgical and hydrometallurgical paths of the traditional element extraction mode, the direct regeneration path has significant economic advantages and sustainability. The direct regeneration methods reported so far can be divided into two types: solid phase repair method and liquid phase repair method according to the different reaction environments. The solid phase repair method mainly drives the thermal diffusion of lithium ions at high temperature to insert them into the crystal structure of retired lithium iron phosphate, thereby regenerating the degraded material. However, due to the large difference in the degree of element loss of batteries with different retirement degrees, unified recycling is very challenging, and long-term high-temperature calcination (600℃~1000℃) will generate large energy consumption. The liquid phase repair method is to mix the S-LFP cathode material powder with lithium salt in a solution environment, and produce a lattice lithiation reaction on the retired lithium iron phosphate through the concentration difference of lithium ions at the solid-liquid interface at a certain temperature and pressure. After the reaction is completed, excess lithium remains in the liquid, and the excess lithium element can be recovered by extraction, which will not cause lithium waste and environmental problems. However, the liquid phase repair methods reported so far usually require the provision of hydrothermal conditions (temperature>80°C) or the introduction of potential difference through electrochemical methods to drive lithium ions to insert into the olivine lattice of retired lithium iron phosphate. The currently reported strategies for liquid phase repair of retired lithium iron phosphate have very slim prospects for commercial large-scale preparation due to the harsh reaction environment. Summary of the invention
[0004] In order to solve the problems of complicated repair methods and high energy consumption in the existing technology of liquid-phase repair of retired lithium iron phosphate and to achieve homogenized cascade repair of lithium iron phosphate with different degrees of retirement, the present application proposes a low-temperature repair technology solution for retired lithium iron phosphate positive electrode materials. By introducing a Lewis base reagent with strong electron donating property, the retired lithium iron phosphate material is lattice relithiated at low temperature, which directly regenerates the retired lithium iron phosphate, thereby greatly reducing the reaction cost and energy consumption. The repaired lithium iron phosphate has excellent performance, the charge and discharge specific capacity at low rate is completely restored, and the discharge specific capacity at high rate is significantly improved, which significantly improves the kinetic transmission characteristics of the failure of retired lithium iron phosphate and has excellent cycle stability at different rates.
[0005] This application adopts the following technical solutions:
[0006] According to the first aspect of the present application, a low-temperature repair method for retired lithium iron phosphate positive electrode materials is provided, comprising the following steps:
[0007] A mixed solution containing retired lithium iron phosphate positive electrode material powder, lithium salt, Lewis base reagent and water is subjected to a liquid phase lithiation reaction.
[0008] Optionally, the Lewis base reagent is selected from at least one of ethanol, thiourea, citric acid, amino acid, catechol, dopamine, hydrogen sulfide, ascorbic acid, potassium borohydride, sodium borohydride, and lithium borohydride.
[0009] Optionally, the conditions of the liquid phase lithiation reaction include: the reaction is carried out under stirring conditions, the stirring speed is 200 to 5000 rpm, the reaction temperature is 20 to 100° C., and the reaction time is 30 to 720 min.
[0010] Optionally, the reaction temperature in the liquid phase lithiation reaction conditions is selected from any value of 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 100°C or any range therebetween.
[0011] Optionally, the concentration of lithium salt in the mixed solution is 0.1 to 5.0 mol / L
[0012] Optionally, the amount of the lithium salt used is 5% to 80% of the molar number of iron atoms in the waste lithium iron phosphate positive electrode material.
[0013] Optionally, the amount of the lithium salt used is 20% to 60% of the molar number of iron atoms in the waste lithium iron phosphate positive electrode material.
[0014] Optionally, the dosage of the Lewis base reagent is 20% to 200% of the molar number of trivalent iron ions in the retired lithium iron phosphate positive electrode material.
[0015] Optionally, the lithium salt is selected from at least one of lithium carbonate, lithium hydroxide, lithium chloride, lithium sulfate, lithium nitrate and lithium acetate.
[0016] The source or preparation method of the retired lithium iron phosphate cathode material powder described in the present application is not strictly limited, and those skilled in the art can select from the prior art as needed. For example, the retired lithium iron phosphate cathode material powder can be prepared by a method comprising the following steps:
[0017] The discarded lithium iron phosphate batteries are unpacked after being discharged, the positive electrode sheets containing active substances are collected and washed to remove the residual electrolyte on the surface thereof, and then the positive electrode sheets containing active substances are ultrasonically treated in water to separate the active substances and the positive electrode sheets, and then the active substances are dried and ground to obtain the retired lithium iron phosphate positive electrode material powder.
[0018] According to a second aspect of the present application, a lithium iron phosphate positive electrode material is provided, characterized in that the lithium iron phosphate positive electrode material is obtained by processing the above-mentioned low-temperature repair method of retired lithium iron phosphate positive electrode material.
[0019] According to a third aspect of the present application, a lithium battery is provided, characterized in that the lithium battery comprises the above-mentioned lithium iron phosphate positive electrode material.
[0020] The beneficial effects of this application include:
[0021] (1) The low-temperature repair method for retired lithium iron phosphate positive electrode materials provided in the present application can directly recover retired lithium iron phosphate at a very low temperature without pressurization, effectively reducing production costs.
[0022] (2) The performance of the lithium iron phosphate after repair using the low-temperature repair method for retired lithium iron phosphate positive electrode materials provided in this application is excellent. The low-rate discharge capacity is restored to the level of commercial lithium iron phosphate, and the high-rate discharge capacity is significantly better than that of retired lithium iron phosphate, and it has excellent cycle stability.
[0023] (3) The low-temperature repair method for retired lithium iron phosphate positive electrode materials provided in this application is compatible with the existing production line of lithium iron phosphate positive electrode materials, and large-scale production can be achieved by adjusting process parameters. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the material structure of X-ray diffraction of the retired (abandoned) lithium iron phosphate positive electrode material after repair in Example 1 of the present application and the retired (abandoned) lithium iron phosphate positive electrode material without repair in Comparative Example 1;
[0025] Figure 2It is a schematic diagram of the material structure of X-ray diffraction of the retired lithium iron phosphate, the lithium iron phosphate reacted with only lithium salt without Lewis base reagent, the lithium iron phosphate reacted with lithium salt and other common Lewis reagents, and the repaired lithium iron phosphate in Comparative Example 1, Comparative Example 2, Comparative Example 3, and Example 1 of the present application;
[0026] Figure 3 The first cycle 0.1C (1C = 170mAg) of the comparative example 1 and the embodiment 1 of the present application -1 ) charge and discharge curves at the rate;
[0027] Figure 4 This is a comparison chart of the discharge specific capacity at different rates between Comparative Example 1 and Example 1 of the present application;
[0028] Figure 5 This is a comparison chart of the discharge specific capacity at different rates of Examples 1 to 4 of the present application;
[0029] Figure 6 This is a cycle performance diagram of button-type half-cells made from the repaired lithium iron phosphate in Example 1 of the present application and the retired lithium iron phosphate in Comparative Example 1 at a rate of 8C. DETAILED DESCRIPTION
[0030] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0031] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0032] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0033] Example 1 (Repairing lithium iron phosphate positive electrode material)
[0034] Collection of retired lithium iron phosphate positive electrode materials: The lithium iron phosphate 18650 cylindrical batteries produced by Shenzhen BYD Power Battery Co., Ltd. are discharged and disassembled after long-cycle decay. The positive electrode sheets are collected and the residual electrolyte on the surface is washed away with ethanol and deionized water. The active materials are separated from the current collectors and ground into powder to obtain retired (discarded) lithium iron phosphate positive electrode materials.
[0035] Repair of retired lithium iron phosphate: Mix 1.0g of retired lithium iron phosphate positive electrode material powder with 0.147g (40% iron atomic ratio) of lithium acetate and 0.2g of thiourea, add 5mL of deionized water, and then carry out liquid phase relithiation process (at a liquid phase reaction temperature of 40°C and a magnetic stirring speed of 700rpm for uniform stirring for 120min). After centrifugal drying, the repaired lithium iron phosphate material is obtained.
[0036] Example 2 (Repairing lithium iron phosphate positive electrode material)
[0037] The difference between Example 2 and Example 1 is that the liquid phase relithiation process includes:
[0038] The liquid phase reaction temperature was adjusted to 25°C.
[0039] Example 3 (Repairing lithium iron phosphate positive electrode material)
[0040] The difference between Example 3 and Example 1 is that the liquid phase relithiation process includes:
[0041] The liquid phase reaction temperature was adjusted to 60°C.
[0042] Example 4 (Repairing lithium iron phosphate positive electrode material)
[0043] The difference between Example 4 and Example 1 is that the liquid phase relithiation process includes:
[0044] The liquid phase reaction temperature was adjusted to 80°C.
[0045] Comparative Example 1 (Retired lithium iron phosphate positive electrode material)
[0046] The collection of retired lithium iron phosphate positive electrode materials is the same as in Example 1, and retired (discarded) lithium iron phosphate positive electrode materials that have not been repaired are obtained.
[0047] Comparative Example 2 (Lithium iron phosphate material after liquid phase reaction with only lithium salt and no Lewis base reagent)
[0048] The collection of retired lithium iron phosphate positive electrode materials is the same as in Example 1.
[0049] The process of repairing retired lithium iron phosphate is different from that of the embodiment in that only lithium salt is added without Lewis base reagent to obtain lithium iron phosphate material.
[0050] Comparative Example 3 (Lithium iron phosphate material after adding other Lewis base reagents for liquid phase reaction)
[0051] The collection of retired lithium iron phosphate positive electrode materials is the same as in Example 1.
[0052] The process of repairing retired lithium iron phosphate is different from that of the embodiment in that both lithium salt and ethanol (a typical example of other Lewis base reagents other than the Lewis base reagents defined in the present application) are added to obtain lithium iron phosphate material.
[0053] Test Example 1
[0054] X-ray diffraction characterization of lithium iron phosphate cathode material sample powder: X-ray powder diffraction test was performed on the retired (abandoned) lithium iron phosphate cathode material after repair in Example 1, the retired (abandoned) lithium iron phosphate cathode material without repair in Comparative Example 1, the lithium iron phosphate material in Comparative Example 2, and the lithium iron phosphate material in Comparative Example 3. The results are as follows Figure 1 , Figure 2 As shown:
[0055] from Figure 1 It can be seen that the XRD spectrum of the unrepaired retired (discarded) lithium iron phosphate positive electrode material powder of Comparative Example 1 has a diffraction peak of an obvious degraded iron phosphate phase due to long-term use, while the degraded iron phosphate phase has completely disappeared in the XRD diffraction spectrum of the unrepaired retired (discarded) lithium iron phosphate positive electrode material powder after repair in Example 1, indicating that the iron phosphate lattice has been re-lithiated in the liquid phase.
[0056] from Figure 2 It can be seen that the X-ray structure diffraction peaks of the lithium iron phosphate material represented by Comparative Example 2, which is obtained by adding only lithium salt and stirring in liquid phase before drying, and the X-ray structure diffraction peaks of the lithium iron phosphate material represented by Comparative Example 3, which is obtained by adding lithium salt and other common Lewis base reagents (such as ethanol) and stirring in liquid phase before drying, the degraded iron phosphate phase in the diffraction patterns of Comparative Examples 2 and 3 did not disappear.
[0057] Test Example 2
[0058] The steps for making the lithium iron phosphate half-cell in this test are as follows:
[0059] (1) Preparation of lithium iron phosphate positive electrode sheets: lithium iron phosphate positive electrode material, conductive agent Super P, and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 8:1:1, and then an appropriate amount of N-methylpyrrolidone (NMP) solvent was added dropwise into a mixing tank and stirred thoroughly to obtain an active slurry. The active slurry was evenly scraped onto an aluminum current collector with a thickness of 15 μm to a thickness of 200 μm. The electrode sheets coated with the slurry were then placed in a vacuum drying oven at 105°C overnight. The electrode sheets were pressed into a thickness of 60 μm using an electric roller press and then cut into small discs with a diameter of 10 mm.
[0060] (2) Assembly of lithium iron phosphate half-cell: Assemble and package the stainless steel positive electrode shell, the lithium iron phosphate positive electrode sheet prepared in step (1), the separator, the lithium negative electrode sheet, the gasket, the spring, and the stainless steel negative electrode shell in this order to prepare a 2032-type button half-cell. The amount of electrolyte added is 30 μL.
[0061] The electrochemical performance test process steps of the lithium iron phosphate half-cell in this test are as follows:
[0062] The battery discharge capacity and cycle stability were tested using a battery tester from Shenzhen Xinweier Electronics Co., Ltd. Before the cycle stability test, the battery was activated three times with a small current of 0.2C, and the operating voltage range was 2.4V to 4.2V.
[0063] Based on the above-mentioned steps for making a lithium iron phosphate half-cell, the retired (abandoned) lithium iron phosphate positive electrode materials repaired in Examples 1 to 4 and the unrepaired retired (abandoned) lithium iron phosphate positive electrode materials of Comparative Example 1 were used as lithium iron phosphate positive electrode materials to make lithium iron phosphate half-cells (wherein the lithium iron phosphate half-cell corresponding to Example 1 is marked as "repaired lithium iron phosphate" and the lithium iron phosphate half-cell corresponding to Comparative Example 1 is marked as "retired lithium iron phosphate"), and electrochemical performance tests were performed respectively, and the results are as follows:
[0064] from Figure 3 It can be seen that the low rate (0.1C) charge capacity of the first cycle of the repaired lithium iron phosphate in Example 1 is restored to 162.9 mAh / g, and the discharge capacity is restored to 158.2 mAh / g, indicating that the lithium loss in the lattice has been completely restored.
[0065] from Figure 4 It can be seen that with the increase of the rate, the discharge capacity advantage of the repaired lithium iron phosphate in Example 1 becomes more and more obvious. At 2.0C, the discharge capacity of the repaired lithium iron phosphate in Example 1 is 137.9 mAh / g, while the retired lithium iron phosphate in Comparative Example 1 only releases a discharge capacity of 118.1 mAh / g due to lattice lithium deficiency and bulk structure degradation.
[0066] from Figure 4 It can be clearly seen that when the rate is increased to the high load state of 8.0C, the discharge capacity of the repaired lithium iron phosphate half-cell in Example 1 can still be retained at 105.3mAh / g, while the discharge capacity of the retired lithium iron phosphate half-cell in Comparative Example 1 is only 43.8mAh / g.
[0067] from Figure 5 It can be seen that the lithium iron phosphate repaired in Example 1 has the highest discharge specific capacity (105.3 mAh / g) at 8.0C compared with other repair conditions.
[0068] from Figure 6It can be seen that the cycle stability of the repaired lithium iron phosphate in Example 1 at 8.0C is far superior to that of the degraded lithium iron phosphate in Comparative Example 1. After 2000 cycles, the repaired lithium iron phosphate in Example 1 can still retain 91.9% of the initial discharge capacity, while the retired lithium iron phosphate in Comparative Example 1 only has 44.4% of the initial capacity retention rate, indicating that the repaired lithium iron phosphate positive electrode material in Example 1 of the present application has good rate performance, excellent high-rate stability, and has a significant performance upgrade effect.
[0069] The electrochemical performance of the lithium iron phosphate after repair in Examples 2 to 4 of the present application is similar to that in Example 1. The repaired lithium iron phosphate has excellent performance, the low-rate discharge capacity is restored to the level of commercial lithium iron phosphate positive electrode, the high-rate discharge capacity is excellent, and it has excellent cycle stability.
[0070] This application achieves direct regeneration by mixing retired lithium iron phosphate cathode materials with an appropriate amount of lithium source and Lewis base reagent in liquid phase, and stirring at room temperature for 2 hours. This technical means has higher economy and environmental sustainability than traditional pyrometallurgy and hydrometallurgy, and is also simpler and more energy-efficient than other direct regeneration methods. In addition, the repaired lithium iron phosphate cathode material has excellent rate performance and high rate cycle stability, achieving performance upgrade.
[0071] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A low-temperature repair method for retired lithium iron phosphate positive electrode materials, characterized in that: The steps include: A mixed solution containing retired lithium iron phosphate positive electrode material powder, lithium salt, Lewis base reagent and water is subjected to a liquid phase lithiation reaction.
2. The low-temperature repair method for retired lithium iron phosphate positive electrode material according to claim 1, characterized in that: The Lewis base reagent is selected from at least one of ethanol, thiourea, citric acid, amino acid, catechol, dopamine, hydrogen sulfide, ascorbic acid, potassium borohydride, sodium borohydride, and lithium borohydride.
3. The low-temperature repair method for retired lithium iron phosphate positive electrode material according to claim 1, characterized in that: The conditions of the liquid phase lithiation reaction include: the reaction is carried out under stirring conditions, the stirring speed is 200-5000 rpm, the reaction temperature is 20-100° C., and the reaction time is 30-720 min.
4. The low-temperature repair method for retired lithium iron phosphate positive electrode material according to claim 1, characterized in that: The concentration of the lithium salt in the mixed solution is 0.1-5.0 mol / L.
5. The low-temperature repair method for retired lithium iron phosphate positive electrode material according to claim 1, characterized in that: The amount of the lithium salt used is 5% to 80% of the molar number of iron atoms in the waste lithium iron phosphate positive electrode material.
6. The low-temperature repair method for retired lithium iron phosphate positive electrode material according to claim 1, characterized in that: The dosage of the Lewis base reagent is 20% to 200% of the molar number of trivalent iron ions in the retired lithium iron phosphate positive electrode material.
7. The low-temperature repair method for retired lithium iron phosphate positive electrode material according to claim 1, characterized in that: The lithium salt is selected from at least one of lithium carbonate, lithium hydroxide, lithium chloride, lithium sulfate, lithium nitrate and lithium acetate.
8. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is obtained by processing the low-temperature repair method for retired lithium iron phosphate positive electrode materials according to any one of claims 1 to 7.
9. A lithium battery, characterized in that: The lithium battery comprises the lithium iron phosphate positive electrode material as claimed in claim 8.